SOLUTION OF PARABOLIC RADON TRANSFORM WITH GIVEN WEIGHT FUNCTION - Djaykov, G.M. (SCIENCE and SOCIETY, 2023)
In this paper we consider the problem of integral geometry on a family of parabolic type with a weight function. An inversion formula for the Fourier image with respect to the first variable is obtained. A sequence of approximate solutions is constructed based on Tikhonov’s regularization.